Epigenetics: The New Frontier in the Landscape of Asthma. (11th May 2016) - Chogtu, Bharti; Bhattacharjee, Dipanjan; Magazine, Rahul
Abstract : Over the years, on a global scale, asthma has continued to remain one of the leading causes of morbidity, irrespective of age, sex, or social bearings. This is despite the prevalence of varied therapeutic options to counter the pathogenesis of asthma. Asthma, as a disease per se, is a very complex one. Scientists all over the world have been trying to obtain a lucid understanding of the machinations behind asthma. This has led to many theories and conjectures. However, none of the scientific disciplines have been able to provide the missing links in the chain of asthma pathogenesis. This was until epigenetics stepped into the picture. Though epigenetic research in asthma is in its nascent stages, it has led to very exciting results, especially with regard to explaining the massive influence of environment on development of asthma and its varied phenotypes. However, there remains a lot of work to be done, especially with regard to understanding how the interactions between immune system, epigenome, and environment lead to asthma. But introduction of epigenetics has infused a fresh lease of life in research into asthma and the mood among the scientific community is that of cautious optimism.